A king and a fool?: the succession narrative as a satire - Miller, Virginia (Biblical interpretation series, 2019)
In A King and a Fool? The Succession Narrative as a Satire Virginia Miller argues that the genre of the Succession Narrative is a satire. Accordingly, this narrative is pejoratively critical of King David. ; Readership: All who are interested in the Succession Narrative, the books of Second Samuel and First Kings, and irony in the Bible